(untitled) (Research in Agriculture Livestock and Fisheries, 2015)
Poinsettia is one of the most important potted plants in the ornamentals industry. The most attractive parts of the poinsettia are its bracts and cyathia. Stem breakage, bract fading, bract edge burn (BEB), bract bruising and bract discoloration reduce its ornamental value. The ornamental value of poinsettia is affected by both pre- and postharvest factors. During cultivation as well as after harvest, sub-optimal or improper supply and / or management of temperature, light, relative humidity, nutrition and hygiene affect the quality of potted poinsettia. A low K : Ca ratio can reduce the incidence of bract necrosis and stem breakage. These disorders are negatively affected by high K and NH4-N fertilizer due to an antagonistic relationship with Ca. Spraying either CaCl2 or Ca(NO3)2 (400mg/l of Ca per week) or a silicon spray (7.12 mM Na2SiO3) and increasing the transpiration rate by reducing the relative humidity can reduce the incidence and severity of bract necrosis. Appropriate variety selection can lessen the risks of leaf drop and BEB. Propagating with thick stemmed cuttings (> 7.5 mm diameter) and carefully watering of plants can also help to prevent stem breakage. The optimum temperature range to achieve expected bract color, size and bud formation during the growth period is 16 to 22oC. Inappropriate light intensity and quality can delay flowering and promote cyathia abscission by decreasing plant carbohydrate status. Ethylene is central to the leaf and cyathia abscission. 1-MCP treatment can be used during short time (2-3 day) transportation to prevent ethylene responses by blocking ethylene receptors. Avoiding rough handling and shortening transportation play an important role in maintaining the quality of harvested poinsettia. The most important pathological problem is Botrytis infection. Low temperatures of 20 to 21oC during cultivation and 10 to 13oC during transport combined with low relative humidity of 60 to 70% RH can reduce infection by Botrytis cinera. Res. Agric., Livest. Fish.2(2): 185-196, August 2015